Proceedings of the 18th Annual International Conference on Digital Government Research 2017
DOI: 10.1145/3085228.3085236
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Trust for Inter-Organizational Information Sharing (IIS) Success in the Public Sector

Abstract: Submission ID: 1099097025File name: ational_Inf ormation_Sharing_IIS_Success_in_the_Public_Sector.pdf (351.79K) Word count: 7584Character count: 43162

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Again, the multisector nature of the partnership and its focus on specific datasets present some specific challenges in terms of trust among participants. Organizations from different sectors have different interests and concerns and they need to trust each other in order to share data and form a successful collaboration [37]. In addition, the fact that the collaboration needs to materialize in the context of sharing of specific datasets that organizations value, could hinder trust development processes.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the multisector nature of the partnership and its focus on specific datasets present some specific challenges in terms of trust among participants. Organizations from different sectors have different interests and concerns and they need to trust each other in order to share data and form a successful collaboration [37]. In addition, the fact that the collaboration needs to materialize in the context of sharing of specific datasets that organizations value, could hinder trust development processes.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in this report and the previous reports in this series, Governing Cross-Border Challenges For instance, the importance of senior leadership support (Yu-Che Chen et al, 2019;Gil-Garcia and Sayogo, 2016;Sayogo, Gil-Garcia and Pardo, 2016), agreeing on common objectives and processes to ensure sustainability up front, funding (Makkonen et al, 2018), ensuring the participation of all relevant stakeholders, mutual benefit (Kurowska-Pysz, Castanho and Loures, 2018), focusing on end-user needs and benefits (Kalvet et al, 2018), prioritising adapting and re-interpreting existing frameworks over creating new ones (Miörner et al 2018), and building trust among partners and stakeholders (Sayogo et al, 2017) have all been shown to be key success factors for cross-border delivery. Yu-Che Chen et al, 2019;Kalvet et al, 2018;Gil-Garcia and Sayogo, 2016).…”
Section: Unpacking Findings and Lessonsmentioning
confidence: 99%
“…Policy, standard and politics [22]- [24], [26]- [31] √ √ √ √ Human resource incapability [11], [21]- [24], [27], [29], [32] √ √ √ √ Lack of governance [6], [27], [33]- [36] √ √ √ √ Expert 1 and 2 from agency A stated that the management support and organizational culture on knowledge sharing are among the challenges that the government team faced during the data integration implementation [36], [37]. Expert 3 and 4 from agency B agreed on this and described as the major obstacle are the top management buy in that will drive the implementation [38], [39].…”
Section: Researchersmentioning
confidence: 99%
“…Data integration team comprises from top management until the technician level should not only being equipped with technical skills but also managerial and communication skills. It is also suggested that past experiences in data integration or any IT projects will benefit the data integration team [11], [22], [32]. Lack of skills in both technical and non-technical area will become a big challenge to execute the data integration implementation.…”
Section: Researchersmentioning
confidence: 99%